2019
DOI: 10.36103/ijas.v50i3.704
|View full text |Cite
|
Sign up to set email alerts
|

Study the Contamination of Some Chemical Pollutants in Hot Foods Stored in Plastic Bags and Containers

Abstract: Plastic food containers and bags are classified as the most dangerous food and water contaminants around the world, because of the possibility to transfer the chemicals from it to food as a result of heating. Therefore this study was aimed to estimate the chemical pollutants (heavy metals included lead, cadmium, arsenic, mercury and zinc) that transfer from plastic food containers and bags to food. Thirty food containers (15 packages and 15 bags) synthesized from Polyethylene Terephthalate (PET) were purchased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The phrase chemical contamination indicates the presence of a chemical where it should not be [11,13]. A chemical hazard may originate from the plate, packaging material, air, water, soil, disinfectants, detergents, pesticides, of from excess levels of metals in or on contaminated meat, vegetables and fruits, infected animals, among others [12,[14][15][16]. However, this chapter does not describe food contaminants as they are not regarded as additives.…”
Section: Indirect Food Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The phrase chemical contamination indicates the presence of a chemical where it should not be [11,13]. A chemical hazard may originate from the plate, packaging material, air, water, soil, disinfectants, detergents, pesticides, of from excess levels of metals in or on contaminated meat, vegetables and fruits, infected animals, among others [12,[14][15][16]. However, this chapter does not describe food contaminants as they are not regarded as additives.…”
Section: Indirect Food Additivesmentioning
confidence: 99%
“…Indirect food contaminants can originate from migration of chemical compounds from plastic food containers or bags when heated; and printed closed packaging materials, glue and adhesives [13]. This is of concern as high concentration in food and water pose serious public health risks especially when the level of migrant chemical is significant [14,[16][17][18]. The growth in agribusiness and globalizations have aided the increasing risk and challenge that has become a global problem [19].…”
Section: Indirect Food Additivesmentioning
confidence: 99%
“…Through the cross-linking provided by this enzyme by linking the polymer chains by the covalent bonds that it forms, and through the studies conducted by the researchers, they found its high potential to improve the properties of the protein membranes, where the cross-linking is one of the most accepted methods of modifying the properties of the protein (1). Most of the studies focused on whey proteins, soybeans, collagen, gelatin, casein, corn zein and wheat gluten as one of the most protein sources used in preparing edible films and coatings (2). Edible films prepared a suitable alternative to Plastic food containers and bags classified under ) Polyethylene Terephthalate ( .…”
Section: Introductionmentioning
confidence: 99%